Awareness and use of systematic literature reviews and meta‐analyses by ministerial policy analysts. (15th June 2017) - Bédard, Pierre‐Olivier; Ouimet, Mathieu
Abstract: Systematic literature reviews and meta‐analyses have been promoted as important types of evidence to inform policy analysis and policy decisions. Little is known, however, about ministerial policy analysts' knowledge of this type of evidence. Drawing from a survey conducted among policy analysts (Québec), we report on the extent to which these research methods and contributions are known and used across policy sectors, and develop a socio‐professional profile of users. We conclude with recommendations for researchers and policy makers to improve the uptake of systematic reviews and meta‐analyses and to more effectively implement evidence‐informed practices.